The Effect of Employee Training and Development on Employee Performance moderated by Job Satisfaction in The North Jakarta Administrative City Water Resources Department - Yani, Ari Soeti; Lukiyana; Prasojo, R. Elly (IJHCM (International Journal of Human Capital Management), 2024)
An employee's performance is closely related to his satisfaction at work. Efforts to improve performance can be made through employee training and development, but in some situations good performance can arise because of the satisfaction felt by employees. The results of the research show that training has a significant effect on employee performance with a t-value of 4.774 > 1.676 and a significant value of the training variable (X1) on employee performance, namely 0.000 < 0.05, employee development has a significant effect on employee performance with a t-count of 2.332 > 1.676 and a value of The employee development variable (X2) is significant on employee performance, namely 0.024 < 0.05, job satisfaction as a moderating variable has a significant effect on employee performance with a t value of 3.692 > 1.676 and the significant value of the job satisfaction variable (Z) on employee performance is 0.001 < 0.05, job satisfaction as a moderating variable strengthens the influence of training on employee performance with a t value of 4.321 > 1.676 and a significant value on the training variable which is moderated by job satisfaction on employee performance, namely 0.000 < 0.05, and job satisfaction as a moderating variable strengthens the influence employee development on employee performance with a t value of 3.349 > 1.676 and a significant value on the employee development variable which is moderated by job satisfaction on employee performance, namely 0.002 < 0.05.